Optimizing smart inverter control for improved distribution network hosting capacity: A model predictive control approach - Muhammad Kamran Khan; Kimmo Kauhaniemi; Hussain Sarwar Khan (International Journal of Electrical Power & Energy Systems)
In this work, we investigate Cos Φ and Q(U) control modes of smart inverters as outlined in EN 50549-standards, aiming to improve the hosting capacity (HC) of a real-world distribution network. To improve the HC, an atomic orbital search (AOS) optimization algorithm is employed to determine optimal location and size of DG, along with optimal control setpoints of smart inverters. Furthermore, we delve into the implementation of direct power finite control set model predictive control (DP-FCS-MPC) aimed at augmenting hosting capacity. DP-FCS-MPC operates by directly using active power (P) and reactive power (Q) as control variables, thus facilitating fast, simple, and decoupled power control without intermediate current loops. The DP-FCS-MPC-based controller regulates the voltage within the targeted limits by tracking the optimal active and reactive power setpoints, directed by the AOS optimizer. The proposed methodology is evaluated using the simulation model of Sundom Smart Grid, a medium voltage distribution network located in Vaasa, Finland. The results confirm the efficacy of the proposed Cos Φ and Q(U) control in improving the HC of the distribution network.